HERMENEUTIKA DIALOGIS: Tanggapan Mehdi Azaiez atas Perkembangan Studi Al-Qur’an Kontemporer - Alfan Shidqon; Fathurrosyid (Jurnal Studi Qur'an dan Tafsir, 2023)
Abstract This article constituates a critical review of Mehdi Azaiez’s scholary work, “Sharing Qur’anic Meanings: Outlines for Dialogical Hermeneutic” (2023), proposing a methodological approach to harmonize contemporary trends in Qur’anic studies, particularly within Western scholarship, termed ‘dialogical hermeneutic’. Employing an explanatory-reflective framework, the review engages rigorously with relevant academic sources. It addresses three pivotal questions: firstly, how does Azaiez articulate dialogical hermeneutic and its applications?; secondly, why is the exploration necessary?; and thirdly, what insights emerge from his endeavors? Findings reveal dialogical hermeneutics as a collaborative approach, merging genealogical, anatomical, and anagnostic models in Qur’anic interpretation, fostering dialogue between Western and Islamic scholarly traditions. Azaiez’s application example in interpreting Surah al-Ikhlaṣ. While the conclusions drawn are still partial, the exposition of the method appears organized, making it potentially applicable for researchers in Qur'anic studies. However, it would be better if Azaiez releases new writings to complement its shortcomings. Keywords: Mehdi Azaiez; dialogical hermeneutic; contemporary Qur’anic studies